(untitled) (Communications in Mathematical Research, 2020)
A Lie 2-bialgebra is a Lie 2-algebra equipped with a compatible Lie 2- coalgebra structure. In this paper, we give another equivalent description for Lie 2-bialgebras by using the structure maps and compatibility conditions. We can use this method to check whether a 2-term direct sum of vector spaces is a Lie 2-bialgebra easily.